Evaluating the Self Activating Concrete Structures Made Up With Nano and Micro Scale Ferromagnetic Materials - Abhishek Boss; Rajbala (International Journal of Scientific Research in Civil Engineering, 2025)
Concrete’s inherent limitations, such as low tensile strength and poor durability, hinder its performance in advanced infrastructure. To resolve this, the research investigates self-healing concrete with nano- and micro-scale ferromagnetic particles (Fe₃O₄) to enhance its functionality. Concrete samples were prepared using different proportions (0%–2.0%) of nano and micro particles. Mechanical tests indicated that Mix M2 (1.0% nano-Fe₃O₄) had the highest 28-day compressive strength of 39.5 MPa, flexural strength of 5.2 MPa, and tensile strength of 3.5 MPa, exceeding the control. Tests for durability indicated high resistance to water (3.9%), acid (3.8%), sulfate (2.7%), and low chloride ion permeability (2450 coulombs). Microstructural SEM examination of M2 exhibited even nanoparticle distribution and fewer microcracks, suggesting better matrix densification. These findings verify that the dual-scale addition of ferromagnetic materials significantly enhances the mechanical, durability, and self-responsive properties of concrete, opening the door to smart, sustainable construction uses.